Dietary and Physical Activity Behaviors Among High School Students — Youth Risk Behavior Survey, United States, 2019 - Merlo, Caitlin L. (MMWR Suppl, 2020)
Establishing healthy dietary and physical activity patterns among youths is an important public health strategy for improving health and preventing chronic diseases; however, few adolescents meet U.S. government recommendations for dietary or physical activity behaviors, and disparities by sex and race/ethnicity exist. CDC analyzed data from the 2019 Youth Risk Behavior Survey to update estimates of dietary and physical activity behaviors among U.S. high school students overall and by sex and race/ethnicity. In addition, 2-year comparisons (2017 and 2019) and trends in prevalence of these behaviors during 2009–2019 were examined. In 2019, overall, during the 7 days before the survey, 41.8% of students had eaten fruit or drunk 100% fruit juices <1 time/day; 40.7% had eaten vegetables <1 time/day; and 16.7% had not eaten breakfast on all 7 days. Moreover, although 57.4% of students had played on ≥1 sports team during the 12 months before the survey, less than half of students had been physically active for ≥60 minutes/day on all 7 days (23.2%), had exercised to strengthen or tone their muscles on ≥3 days/week (49.5%), had met both aerobic and muscle-strengthening physical activity guidelines (16.5%), or had attended physical education classes on all 5 days in an average school week (25.9%). Trend data indicate limited progress in shifting dietary and physical activity behaviors. That is, with the exception of decreases in the percentage of students who had consumed soda ≥1 time/day (2009: 29.2%; 2019: 15.1%), sports drinks ≥1 time/day (2015: 13.8%; 2019: 10.6%), and <3 glasses/day of plain water (2015: 50.5%; 2019: 44.6%), high school students’ dietary and physical activity behaviors have not improved and, in certain cases, have worsened. These findings support the need for multicomponent approaches, including policy and environmental changes, and opportunities for adolescents to learn about and practice making healthy choices.